Decision-making rationales among Quebec VET student aged 25 and older - Louis Cournoyer; Frédéric Deschenaux (International Journal for Research in Vocational Education and Training (IJRVET), 2017)
Each year, a large number of students aged 25 years and over take part in vocational and education training (VET) programs in the Province of Quebec, Canada. The life experiences of many of these adults are marked by complex psychosocial and professional events, which may have influenced their career decision-making processes. This paper aimed to identify key rationales guiding the decisions of adults aged 25 years and older to return to education based on a thematic analysis of 30 semi-structured interviews with students enrolled in a VET program. The analysis focused on two theoretical axes: one biographical and the other interactionist. The first involved personal life courses and professional projects undertaken by the student in the past. The second examined tensions and conflicts between context forces and adjustment strategies adopted by the student. The results revealed five decision-making rationales that characterized the vast majority of the students' experiences: 1) get out of a socioprofessional and economic slump; 2) know yourself better, personally and socially; 3) value the concrete and the practical; 4) take advantage of supporting conditions; and 5) reconcile proximity and the known. The relevance and implications of these findings for professionals and decision makers in vocational training are discussed.
Keywords: 330; VET; Vocational Education and Training; Vocational Training; Adults; Decision-Making; Qualitative; Life-Course